Novel Affibody Molecules Targeting the HPV16 E6 Oncoprotein Inhibited the Proliferation of Cervical Cancer Cells - Zhu, Jinshun; Kamara, Saidu; Wang, Qi; Guo, Yanru; Li, Qingfeng; Wang, Linlin; Chen, Jingjing; Du, Qianqian; Du, Wangqi; Chen, Shao; Zhu, Shanli; Chen, Jun; et al. (Frontiers in Cell and Developmental Biology, 2021)
Despite prophylactic vaccination campaigns, high-risk human papillomavirus (HPV)-induced cervical cancer remains a significant health threat among women, especially in developing countries. The initial occurrence and consequent progression of this cancer type primarily rely on, E6 and E7, two key viral oncogenes expressed constitutively, inducing carcinogenesis. Thus, E6/E7 have been proposed as ideal targets for HPV-related cancer diagnosis and treatment. In this study, three novel HPV16 E6-binding affibody molecules (ZHPV16E61115, ZHPV16E61171 and ZHPV16E61235) were isolated from a randomized phage display library and cloned for bacterial production. These affibody molecules showed high binding affinity and specificity for recombinant and native HPV16 E6 as determined by surface plasmon resonance (SPR), indirect immunofluorescence, immunohistochemistry (IHC) and near-infrared small animal optical imaging in vitro and in vivo. Moreover, by binding to HPV16 E6 protein, ZHPV16E61235 blocked E6-mediated p53 degradation, which increased the expression of some key p53 target genes, including BAX, PUMA and p21, and thereby selectively reduced the viability and proliferation of HPV16-positive cells. Importantly, ZHPV16E61235 was applied in combination with HPV16 E7-binding affibody ZHPV16E7384 to simultaneously target the HPV16 E6/E7 oncoproteins, and this combination inhibited cell proliferation more potently than either modality alone. Mechanistic studies revealed that the synergistic antiproliferative activity depends primarily on the induction of cell apoptosis and senescence but not cell cycle arrest. Our findings provide strong evidence that three novel HPV16 E6-binding affibody molecules could form a novel basis for the development of rational strategies for molecular imaging and targeted therapy in HPV16-positive preneoplastic and neoplastic lesions.